2013
DOI: 10.1186/1735-2746-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of estimated daily intake (EDI) of cadmium and lead for rice (Oryza sativa L.) in calcareous soils

Abstract: The excessive amounts of cadmium and lead in food chain can cause health problems for humans and ecosystem. Rice is an important food in human diet. Therefore this study was conducted in order to investigate cadmium and Lead concentrations in seed rice (Oryza saliva) of paddy fields in southwest of Iran. A total of 70 rice seed samples were collected from paddy fields in five regions of Khuzestan province, Southwest Iran, during harvesting time. In the samples cadmium and Lead concentrations were measured. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…To assess the public health risks, these weekly intake were compared with the Provisional Tolerable Weekly Intake (PTWI), recommended by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). This index shows appropriate safe exposure levels and is used to estimate the amount of contaminants, ingested over a lifetime without appreciable risk (Chamannejadian et al, 2013). The European Food Safety Autority (EFSA) has established regulatory guidelines, the PTWI of Cd and Pb Trace elements concentrations (mean, standard deviation, minimum and maximum) in the muscle tissues of swordfish are shown in Table 2.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…To assess the public health risks, these weekly intake were compared with the Provisional Tolerable Weekly Intake (PTWI), recommended by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). This index shows appropriate safe exposure levels and is used to estimate the amount of contaminants, ingested over a lifetime without appreciable risk (Chamannejadian et al, 2013). The European Food Safety Autority (EFSA) has established regulatory guidelines, the PTWI of Cd and Pb Trace elements concentrations (mean, standard deviation, minimum and maximum) in the muscle tissues of swordfish are shown in Table 2.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…Seed and soil samples were analyzed according to the standard laboratory procedures. All measurements and explanations in the current study were provided by the same authors (14). Data sets were analyzed with different software packages.…”
Section: Objectivesmentioning
confidence: 99%
“…Similar researches were also conducted by the same technique such as Gholap and Sanap et al but some recent researches reported different parameters such as the high percentage of lime that can play an important role in the behavior of Cd. Further researches by the same authors should address the relationship between the concentrations of Cd in rice seeds and soil (3,14). Abbreviations: CV, coefficient of variation; SD, standard deviation; TNV, total neutralizing value.…”
Section: Descriptive Statistic Parametersmentioning
confidence: 99%
“…The availability of Pb in paddy soil is of increasing concern due to Pb toxicity from human consumption of rice (Chamannejadian et al 2013). The uptake and accumulation of trace elements by plants are governed by both soil and plant factors, and they differ significantly with plant species.…”
Section: Introductionmentioning
confidence: 99%